Correlation between Individual Characteristics and Workload toward Occupational Stress of Social Undesirables Facilitators - Siti Anisah; Mulyono Mulyono (Universitas Airlangga, 2020)
Introduction: Prevalence occupational stress continues to increase. Based on survey in 2012, there was 64% workers in Indonesia suffered increased stress compared to previous year. According to the Great Britain 2017 statistics, jobs with higher than average rates of stress are health workers and social workers. Several factors that can affect occupational stress are individual characteristics and workload. The aim of this study is to analyze the relationship of individual characteristics (age, sex, education level, and working period) and workloads (physical and mental workloads) toward the level of occupational stress of social undesirables facilitators at Regional Technical Implementation Unit Social Shelter Keputih Surabaya. Methods: This study was observational research and used cross-sectional method. Sample in this research was 21 workers. The sample were taken used total sampling. The writer used contingency coefficient for analyzing variables relation. Results: The study showed the age (coefficient= 0.572) and mental workload (coefficient= 0.420) had a moderate relation toward occupational stress level. Sex (coefficient= 0.136) had the lowest relation toward occupational stress level. The education level (coefficient= 0.398), working period (coefficient= 0.298), and physical workload (coefficient= 0.209) had a low relation toward occupational stress level. Conclusion: The individual characteristic (age) and workload (mental workload) related to occupational stress.Keywords: individual characteristics, occupational stress, workload